Development of Encyclopedia Boyong Sleman Insekta River as Alternative Learning Resources - Fitriani, Rini Dita; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2020)
This study aims to determine the types of insects Coleoptera, Hemiptera, Odonata, Orthoptera and Lepidoptera in the Boyong River, Sleman Regency, Yogyakarta, to develop the Encyclopedia of the Boyong River Insect and to determine the quality of the encyclopedia developed. The method used in the research inventory of the types of insects Coleoptera, Hemiptera, Odonata, Orthoptera and Lepidoptera insects in the Boyong River survey method with the results of the study found 46 species of insects consisting of 2 Coleoptera Orders, 2 Hemiptera Orders, 18 orders of Lepidoptera in Boyong River survey method with the results of the research found 46 species of insects consisting of 2 Coleoptera Orders, 2 Hemiptera Orders, 18 orders of Lepidoptera in Boyong River survey method. odonata, 4 Orthopterous Orders and 20 Lepidopterous Orders from 15 families. The encyclopedia that was developed was created using the Adobe Indesig application which was developed in printed form. Testing the quality of the encyclopedia uses a checklist questionnaire and the results of the percentage of ideals from material experts are 91.1% with very good categories, 91.7% of media experts with very good categories, peer reviewers 92.27% with very good categories, biology teachers 88, 53% with a very good category and students 89.8% with a very good category. Based on these results, the encyclopedia is appropriate to be used as an alternative source of learning.